Modeling of soil organic carbon loss by water erosion on a tropical watershed - Lense, Guilherme Henrique; Moreira, Rodrigo; Parreiras, Taya; Avanzi, Junior; Mincato, Ronaldo (Revista Ciência Agronômica, 2021)
ABSTRACT - Water erosion under tropical climate conditions is one of the main processes that change the balance between the inputs and outputs of soil organic carbon (SOC). Water erosion modeling using the Erosion Potential Method (EPM) can be used as an alternative to assist in understand soil carbon dynamics and its interaction with the erosive process. In this context, we performed a simple approach to calculate carbon losses by water erosion in a subbasin with a wide land-use diversity. We tested the hypothesis that the EPM combined with the spatial distribution of SOC content can be useful to estimate the organic carbon removal by water erosion with satisfactory efficiency in a tropical region of Brazil. The results showed that from 126.53 Mg year-1 of the total eroded organic carbon estimated, 111.60 Mg year-1 were deposited in relief depressions, while 14.93 Mg year-1 reached the water body system. The applied methodology represents a cost-effective and relatively fast method to estimate the soil organic carbon loss by water erosion and allows the determination of the areas that most need intervention, aiming to decrease the impact of agriculture on greenhouse gas emissions. The main advantage of this method is the little input data requirement, which increases the possibility of application in poorly studied regions.